Survey of the Dynamic Modeling Methods of Light Vehicles - Deák, Krisztián; Hajdu, Sándor; Szántó, András (International Journal of Engineering and Management Sciences, 2020)
Vehicle dynamics models can be classified into two groups based on the model simplification. There are simplified models based on neglections, these models do not contain all body directions: longitudinal, lateral and vertical directions. There are several reasons for the simplification: control, estimation and analysis methods can be used only with simplified models, or another reason is the computational cost. Apart from simplified models, there are detailed/truth vehicle dynamics models which aim is to provide a virtual plant of the real vehicle for virtual prototype-based development. In this paper, some simplified vehicle models are presented, after a short introduction.